ANALISIS RASIO RODA GIGI MOBIL LISTRIK 1 KW TERHADAP AKSELERASI - Mukhamad Khumaidi Usman (Politeknik Harapan Bersama Tegal, 2023)
the use of fossil-fuel vehicles/cars has a negative impact on the environment and health, one of which is the trigger for global warming to get worse as more and more fossil fuel-fueled vehicles increase. To overcome this, many countries are starting to switch to zero emission vehicles, namely electric car vehicles. Electric vehicles have the same performance and acceleration power as conventional vehicles as long as the main components of the vehicle are met, such as the use of motors, batteries, controllers and gear ratios that match the required performance, use of gear ratios to acceleration using 1 kW motors, battery capacity 48 volts, 57 Ah, from the test results at a ratio of 14: 44 without load it was obtained a value of 228.7 rpm while with a load obtained a speed of 29 km/hour the time needed was 06.09 seconds.